THE ROLE OF INFORMATION MODELING IN THE EFFECTIVE MANAGEMENT OF AN OIL REFINING ENTERPRISE (REVIEW) - Brednikov, Andrii; Makarenko, Oleh; Okhrimenko , Tetiana (Science-based technologies, 2023)
The article substantiates the need for the use and implementation of an information model in the strategic management of an oil refining enterprise. The main components, requirements and potential directions of using the information model for the management of the oil refining enterprise (RE) are analyzed. The strategic advantages of applying this model as a basis for building algorithms for automating business processes of the RE have been determined. The advantages of implementing this model in the software environments of modern ERP systems are formulated. This will facilitate the automatic collection and processing of data, automation of routine tasks, implementation of electronic document management and improved communication between different functional areas. This will lead to shorter process times, fewer errors and an increase in overall enterprise efficiency. An information model is a conceptual model that defines the structure, elements and relationships of information flows in an enterprise. It is a key element of the enterprise’s engineering and is used to seamlessly understand the needs and support the design of its information systems. Also the advantages of integrating the above-mentioned improved modeling structure, which will allow more effective management of operations, resources and activities of the oil refining enterprise, are analyzed. In addition, an information management model can help reduce costs and improve customer service. By providing more accurate and faster results, the refinery can easily keep pace with the rapid changes in the industry. It will also automate many routine processes and ensure their optimal functioning, provide advanced analytical tools for data evaluation and forecasting of situations, enable informed decisions based on actual data and improve the efficiency of the enterprise.Keywords: oil refining enterprise, optimization, information model of enterprise management.